Contributions from coherent and incoherent lattice excitations to ultrafast optical control of magnetic anisotropy of metallic films - Kats, Vladimir N.; Linnik, Tatiana L.; Salasyuk, Alexey S.; Rushforth, Andrew W.; Wang, Mu; Wadley, Peter; Akimov, Andrey V.; Cavill, Stuart A.; Holy, Vaclav; Kalashnikova, Alexandra M.; Scherbakov, Alexey V. (SPIE, 2016)
Spin-lattice coupling is one of the most prominent interactions mediating response of spin ensemble to ultrafast optical excitation. Here we exploit optically generated coherent and incoherent phonons to drive coherent spin dynamics, i.e. precession, in thin films of magnetostrictive metal Galfenol. We demonstrate unambiguously that coherent phonons, also seen as dynamical strain generated due to picosecond lattice temperature raise, give raise to magnetic anisotropy changes of the optically excited magnetic film; and this contribution may be comparable to or even dominate over the contribution from the temperature increase itself, considered as incoherent phonons.